What's special about space?. (29th September 2022) - Parr, Thomas
Abstract: This commentary suggests that, although Markov blankets may have different interpretations in different systems, these distinctions rest not upon the type of blanket, but upon the model that determines the blanket. As an example, the conditions for a model in which the Markov blanket may be interpretable as a physical (spatial) boundary are considered.